A Clinical Study to Evaluate the Effect of Gharshana Karma (Microdermabrasion) in Mukhdushika (Acne Vulgaris) (AYUSHDHARA, 2022)
Ayurveda classic has mentioned various diseases. Mukhdushika is explained by Acharaya Shushrut in Nidansthan. It can be correlated with Acne vulgaris. Acne vulgaris is the most common skin disease of the youth especially in the puberty age. One of the most common complication of acne is scarring. It has been found to have a significant impact on their psychological well-being and has been associated with depression and suicidal ideation. Acne causes emotional upset and impact to the patient by disfiguring face and scarring skin. Gharshan karma with Samudraphen has been described in Astang Hridya. In the modern medical science this technique closely resembles microdermabration (MDA), which is a resurfacing technique. Aim: To study the efficacy and safety of microdermabration (MDA) in managing acne vulgaris at Skin Care Unit, R.G.G.P.G. Ayurvedic College, Paprola, Kangra (H.P.). Materials and Methods: Based on inclusion and exclusion criteria 30 patients with acne scars, who visited the hospital outdoor patient department were included in the study. All patients were treated with MDA for 12 sittings, 2 weeks apart. Results: Out of 30 patients, 1 (3%) patient got excellent improvement, 18 (60%) patient got good improvement, 10 (33.3%) patient got fair improvement and 1 (3%) patient got poor improvement.